Supercritical CO2 environment service X65 pipeline steel and manufacturing method thereof
By using ultra-low Cr content design and Mn-Cu-Ni-Mo multi-alloy and Nb-Ti-V microalloy in CO2 pipeline materials, a refined structure is formed, which solves the problems of fracture, low-temperature toughness and corrosion resistance of pipeline materials in supercritical CO2 environment, and achieves high strength, good welding properties and excellent low-temperature and corrosion performance.
Patent Information
- Application Number
- CN202311374000.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
The existing CO2 pipeline materials have problems such as risk of fracture failure, insufficient low-temperature toughness and poor corrosion resistance in supercritical CO2 environments.
The ultra-low Cr content design is adopted, combined with Mn-Cu-Ni-Mo multi-alloy and Nb-Ti-V microalloy, through refined component control and process processing, a uniformly refined granular bainite + block ferrite + pearlite + MA structure is formed, improving the strength and toughness of the material and the resistance to CO2 corrosion.
The excellent performance of pipeline steel in supercritical CO2 environment is achieved, including high yield strength, tensile strength, good welding performance, significantly improved low-temperature toughness and corrosion resistance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal materials and their manufacture, and specifically relates to an X65 pipeline steel serving in a supercritical CO2 environment and a manufacturing method thereof. Background Art
[0002] CCUS (Carbon Capture, Utilization and Storage) technology has become the focus, and CO2 storage and transportation is an important part of it. For long-distance and large-scale CO2 transportation, supercritical CO2 pipeline transportation is the most cost-effective transportation method. Supercritical CO2 has a greater risk of fracture failure than conventional gaseous CO2 or natural gas pipelines. Because the supercritical state reaches a high saturation pressure, and CO2 is prone to phase change during the decompression process, this will cause the decompression wave curve to change from a smooth curve to a curve with a pressure platform, and the decompression wave velocity will be greatly reduced, making it more likely to have fast-propagating ductile fractures, and crack arrest is more difficult, so higher requirements are placed on the fracture performance of the pipe.
[0003] In addition, under low-temperature conditions such as pipeline leakage or planned / accidental pressure reduction, the temperature may drop due to the Joule-Thomson effect, and the material may be exposed to low temperatures of -40°C, or even below the triple point (-56°C). The pressure reduction of long pipe sections may be maintained for a long time. If the temperature is low enough, the pipeline material is prone to become brittle, which puts higher requirements on the low-temperature performance of the material. Therefore, the pipeline for transporting carbon dioxide should have sufficient low-temperature toughness.
[0004] In addition, supercritical CO2 is more soluble in water and more corrosive than conventional gaseous CO2, especially in the presence of trace gas impurities, such as H2S and other hydrogen atom impurities that may react with O2 to generate water under certain conditions, and the presence of SO2, CO or trace NO2, etc., will accelerate corrosion problems. Even under the service conditions of pipelines after gas source treatment, due to the complex actual operating environment, including various gas source impurities and unplanned working conditions, which may lead to potential corrosion risks, it is necessary to consider the tolerance of materials under unqualified water content conditions.
[0005] Chinese patent CN202110097162.1 discloses "a steel plate resistant to CO2 corrosion and a preparation method". The components and weight percentages of the pipeline steel are: C: 0.03-0.07%, Cr: 4.0-6.0%, Ni: 0.15-2.50%, Nb: 0.01-0.06%, P≤0.005%, S≤0.005%, and the rest are Fe and unavoidable impurities. More Cr and Ni are added to ensure that the material has good CO2 corrosion resistance and low-temperature toughness, and the alloy cost is relatively high. The yield strength of the steel plate is ≥460MPa, the tensile strength is ≥510MPa, the Charpy impact energy at -20℃ is ≥80J, and the corrosion rate in the simulated CO2 flooding oil production equipment service environment is ≤0.21mm / a.
[0006] Chinese patent CN201310217916.8 discloses "CO2 corrosion-resistant pipeline steel for ground gathering and transportation and its preparation method". The composition of the steel plate is as follows by weight percentage: C: 0.01-0.08%, Si: 0.10-0.50%, Mn: 0.50-1.50%, P≤0.02%, S≤0.006%, Nb+V+Ti≤0.1%, Cr: 1.0-3.0%, Mo: 0.10-0.30%, Cu: 0.10-0.50%, Ni: 0.10-0.50%, and the rest is Fe and unavoidable impurities. Alloy elements such as Cr, Nb, V, Ti and Mo are added in the patent. Cr and Mo are both precious metal elements. In addition, Cr is not good for welding performance. The tensile strength of the steel plate is 600-700Mpa, the yield strength is 530-600Mpa, the total elongation is ≥23%, the yield strength ratio is ≤0.85, and the impact energy at -20℃ is ≥220J. The corrosion performance can meet the corrosion of CO2 saturated state under normal pressure.
[0007] Chinese patent CN201510650858.7 discloses "a pipeline steel with excellent CO2 corrosion resistance and production method", and its chemical composition and mass percentage are as follows: C: 0.035-0.060%, Si: 0.10-0.30%, Mn: 1.00-1.50%, P≤0.012%, S≤0.0020%, Cr: 3.0-4.5%, Cu: 0-0.10%, Ni: 0-0.10%, Mo: 0-0.10%, Nb: 0.015-0.040%, Ti: 0.010-0.025%, Al: 0.010-0.050%, N: ≤0.008%, and the rest are iron and unavoidable impurity elements. The patented alloy scheme also adds more Cr (3.0-4.5%), resulting in increased costs and reduced welding performance. The yield strength of the steel plate (R t0.5 )≥450MPa, tensile strength (R m)≥535MPa, -20℃KV2≥120J, -15℃DWTTSA≥85%. Under the test conditions of temperature 80℃, CO2 partial pressure reaching 2MPa, and flow rate of 1.0m / s, the corrosion rate is ≤5mm / a.
[0008] Chinese patent CN201610897282.9 discloses "a low-Cr economical X65 pipeline steel resistant to CO2 corrosion and a production method", whose chemical composition and mass percentage are as follows: C: 0.04-0.05%, Si: 0.18-0.22%, Mn: 0.5-0.6%, Cr: 0.1-0.2%, Mo: 0.1-0.15%, Nb: 0.035-0.050%, V: 0.020-0.030%, Ti: 0.010-0.020%, P≤0.01%, S≤0.003%, and the rest are Fe and unavoidable impurities; and meet Nb+V+Ti≤0.1%. Steel plate yield strength R t0.5 460~500MPa, tensile strength R m 550~600MPa, yield strength ratio R t0.5 / Rm≤0.9, elongation after break A 50 mm≥18, -20℃ impact energy KV2≥120J, -15℃ fracture shear surface ratio DWTT SA≥85%; at a temperature of 60℃, CO2 partial pressure of 1MPa, and a flow rate of 1.0m / s, the corrosion rate is ≤0.5mm / year. It is difficult to effectively ensure stable strength and low-temperature toughness, the low-temperature toughness is relatively poor, and the corrosion resistance of the material is also reduced.
[0009] From the comparison with the existing patents, it can be found that most of the existing CO2 pipeline transportation materials use a higher Cr content, which not only significantly increases the alloy cost, but also the increased Cr content leads to higher temper brittleness, which is easy to crack during welding, resulting in poor weldability and a greater performance risk for long-distance pipelines. In addition, although some materials use a lower Cr content, there are no better corresponding measures to compensate for the performance loss, and the low-temperature toughness and corrosion resistance are relatively poor. Summary of the invention
[0010] The object of the present invention is to provide an X65 pipeline steel for service in a supercritical CO2 environment and a method for manufacturing the same. The obtained pipeline steel can reach the X65 strength level, has good weldability, excellent low temperature toughness and corrosion resistance, and the R t0.5 Yield strength 450~570MPa, tensile strength 540~700MPa, yield strength ratio ≤0.93, A 50mm elongation ≥ 35%, -56℃ Charpy impact energy KV8 ≥ 300J, -46℃ DWTT SA% ≥ 85%, average corrosion rate in supercritical CO2 phase under 8MPa, 50℃ saturated water conditions ≤ 0.06mm / a.
[0011] To achieve the above object, the technical solution of the present invention is:
[0012] An X65 pipeline steel for supercritical CO2 environment, the chemical composition weight percentage of which is C: 0.02-0.07%, Si: 0.10-0.30%, Mn: 0.80-1.45%, P≤0.0080%, S≤0.0015%, Cu: 0.05-0.35%, Ni: 0.05-0.30%, Cr: 0.20-0.80%, Mo: 0-0.09%, Nb: 0.02 5~0.055%、V:0~0.05%、Ti:0.005~0.020%、Ca:0.0010~0.0040%、Alt:0.010~0.040%、B≤0.0004%、O≤0.0030%、N≤0.0050%、H≤0.0002%、Ce:0.0005~0.0050%、the balance includes Fe and other unavoidable impurities, and at the same time meet the following requirements:
[0013] Ca / S≥1.5;
[0014] Nb+V+Ti≤0.12%;
[0015] 0.8≤(Nb+V+Ti) / (C+N+5×B)≤2.5;
[0016] (Cr+Cu / 3+Ni / 3+Mo+Ce×25) / (S+P)≥50.
[0017] Furthermore, the balance is Fe and other inevitable impurities.
[0018] The microstructure of the pipeline steel of the present invention is uniformly refined granular bainite+blocky ferrite+pearlite+MA, wherein the content of granular bainite is ≥85%.
[0019] The R of the pipeline steel of the present invention t0.5 Yield strength 450~570MPa, tensile strength 540~700MPa, yield strength ratio ≤0.93, A 50 mm elongation ≥ 35%, -56℃ Charpy impact energy KV8 ≥ 300J, -46℃ DWTT SA% ≥ 85%, average corrosion rate in supercritical CO2 phase under 8MPa, 50℃ saturated water conditions ≤ 0.06mm / a.
[0020] In the chemical composition design of X65 pipeline steel for service in supercritical CO2 environment of the present invention:
[0021] C: The most economical strengthening element in steel, which improves the strength of steel through interstitial solid solution strengthening. Increasing the carbon content can greatly improve the hardenability of steel, reduce the amount of other precious alloys added, and reduce production costs, but the increase in C content is not good for the ductility, toughness, weldability and corrosion resistance of steel. Therefore, the present invention adopts an ultra-low C design, and its content is controlled at 0.02-0.07%.
[0022] Si: solid solution strengthening element, also a deoxidizing element in steel, but too high a content will have an adverse effect on surface quality and welding performance, and if the Si content exceeds 0.30%, toughness may decrease. Therefore, in the present invention, the Si content is controlled at 0.10-0.30%.
[0023] Mn: It improves the strength of steel by solid solution strengthening. It is the most important and economical strengthening element in steel to compensate for the strength loss caused by the reduction of C content. Mn helps to obtain fine phase transformation products and also helps to control oxygen and sulfur in the steelmaking process. If the Mn content is low, it is difficult to obtain the target strength level, but Mn will also aggravate the center segregation. Therefore, in the present invention, the Mn content is controlled at 0.80-1.45%.
[0024] Cr: It has a certain solid solution strengthening effect and can effectively improve the hardenability of steel. When the Cr content is above 0.10%, it can effectively improve the corrosion resistance of steel and form a relatively dense protective layer on the surface of the steel to protect the matrix. However, when the Cr content in the steel is too high, it is not conducive to the quality of the weld and is prone to form gray spot defects. Therefore, the Cr content in the present invention is controlled at 0.20-0.80%.
[0025] Nb: An important element of low-carbon microalloyed steel. During the hot rolling process, the solid-dissolved Nb strain-induced precipitation forms Nb carbonitrides, which pin the grain boundaries to inhibit the growth of deformed austenite. After controlled rolling and controlled cooling, the deformed austenite is transformed into a fine product with a high dislocation density. After the steel strip is coiled, the solid-dissolved Nb will be dispersed and precipitated in the matrix as the second phase particle NbC, which plays a role in precipitation strengthening. More Nb makes the slab prone to cracks, thereby affecting the surface quality, and also deteriorates the welding performance. Therefore, the Nb content in the present invention is controlled at 0.025-0.055%.
[0026] Ti: a good deoxidizing and degassing agent and an effective element for fixing nitrogen and carbon. The undissolved carbonitrides of Ti can prevent the growth of austenite grains when the steel is heated. The TiN and TiC precipitated during rough rolling in the high-temperature austenite region can effectively inhibit the growth of austenite grains and refine the grains. At the same time, they can also increase the solid solubility of Nb and reduce the microcrack sensitivity of Nb-containing steel. It is generally added in combination with Nb. In addition, the precipitation during the welding process can also inhibit the growth of high-temperature grains and improve the welding performance. Therefore, the Ti content in the present invention is controlled at 0.005-0.020%.
[0027] V: Vanadium has a strong affinity with carbon, ammonia, and oxygen, and forms corresponding stable compounds with them. Vanadium exists in steel mainly in the form of carbides. Vanadium can refine the grain structure of steel, increase the grain coarsening temperature of steel, improve the strength and low-temperature toughness of steel, and improve the post-weld toughness of steel and welding performance. However, excessive V content will lead to an increase in the tough-to-brittle transition temperature of steel. Therefore, the V content of the present invention is controlled at 0 to 0.05%.
[0028] Nb+V+Ti: More Nb, V, and Ti can form dispersed carbon-nitrogen-boron compounds with C, N, and B. These carbon-nitrogen-boron compounds can exert a solid solution strengthening effect. Since these carbon-nitrogen-boron compounds have a high melting point, they act as foreign crystal nuclei in the subsequent preparation process, and can effectively refine the grain size and improve the structural properties. However, the addition of more Nb, V, and Ti can easily lead to the aggregation of carbonitride particles in the steel plate, especially in the core, where long strips of carbonitride particles are formed along the rolling direction. These particles are hard phases with a higher hardness than the matrix, which increases the local brittleness of the structure and deteriorates the low-temperature toughness of the material. Therefore, in the present invention, Nb+V+Ti is controlled to be ≤0.12%.
[0029] In addition, the combination of Nb, V, Ti and C, N, and B can effectively inhibit Cr from generating carbon, nitrogen, and boron compounds. On the one hand, it can reduce the impact of the reduction in toughness and strength caused by the carbon, nitrogen, and boron compounds of Cr. On the other hand, it improves the solid solution of Cr and gives full play to the role of Cr in CO2 corrosion resistance. Therefore, the ratio of Nb, V, Ti to C, N, and B needs to be strictly controlled. In the present invention, it is necessary to control 0.8≤(Nb+V+Ti) / (C+N+5×B)≤2.5. When (Nb+V+Ti) / (C+N+5×B)>2.5, the second phase particles are coarse and unevenly distributed, which is easy to cause stress concentration and brittle fracture, and significantly reduce the low-temperature toughness of the parent material and the weld. When (Nb+V+Ti) / (C+N+5×B)<0.8, the number of precipitated phases is small, and the size is too small, which is easy to be dissolved into the parent material again, and the grain boundary pinning effect is weak, which has an adverse effect on low-temperature toughness. At the same time, the solid solution of Cr is reduced, and the CO2 corrosion resistance is weakened.
[0030] Mo: A strong hardenability element, which significantly delays the ferrite phase transformation, inhibits the formation of ferrite and pearlite, and can effectively promote the bainite transformation to strengthen the matrix and obtain a finer structure. A certain amount of Mo has obvious benefits for improving the material structure and properties, but when the Mo content is too high, the plasticity of the steel is reduced, and the cost of Mo is high. Therefore, in the present invention, the Mo content is controlled at a relatively low level of 0 to 0.09%.
[0031] Cu and Ni: can improve the strength of steel through solid solution strengthening and improve the atmospheric corrosion resistance of steel, but a high content will cause hot cracks in the steel plate, while Ni can refine the grains and improve the hot brittleness easily caused by Cu in steel, which is significantly helpful for improving low-temperature toughness. Therefore, in the present invention, the Cu content is controlled at 0.05-0.35%, and the Ni content is controlled at 0.05-0.30%.
[0032] S and P: the main impurity elements in steel. Phosphorus easily causes cold brittleness of steel, and sulfur easily causes hot brittleness, resulting in unstable performance of steel. In particular, as the S content increases, the number of MnS inclusions increases, which significantly reduces the low-temperature toughness of the material. Therefore, the phosphorus and sulfur content in steel should be reduced as much as possible. Therefore, in the present invention, S is controlled to be ≤0.0015% and P ≤0.0080%.
[0033] Ca: Ca treatment can control the morphology of sulfides, improve the anisotropy of steel plates, and increase low-temperature toughness; in addition, when the S content is high, Ca / S needs to be appropriately increased to reduce MnS inclusions in the steel, but too high a Ca content can easily lead to an increase in inclusions such as CaO in the steel. In the present invention, the Ca content is controlled at 0.0010-0.0040%, and Ca / S is controlled to be ≥1.5.
[0034] Alt: Al is used for deoxidation of steel. A proper amount of Al is also beneficial for grain refinement and improving toughness. However, if the Al content is greater than 0.05%, coarse precipitates may be formed, thereby reducing the low-temperature toughness of the steel. Therefore, the Alt content of the present invention is controlled at 0.010-0.040%.
[0035] N, O, H: For low-temperature toughness, O, N and H may all lead to brittle fracture, especially at low temperatures. The presence of O and N will form O compounds and N compounds, which may aggregate at the grain boundaries, leading to intergranular brittleness. At the same time, H may also penetrate into the grains, causing lattice deformation and hole formation, leading to brittle fracture. Therefore, the low-temperature toughness of steel is related to the content of O, N, and H. Excessive or inappropriate content may lead to brittle fracture. Therefore, in the present invention, O≤0.0030%, N≤0.0050%, and H≤0.0002% are controlled.
[0036] B: The main function of B in steel is to increase the hardenability and strength of steel, thereby saving other rare and precious metals, but the addition of B element will have a significant adverse effect on the low-temperature toughness of the material. Therefore, in the present invention, B is controlled to be ≤0.0004%.
[0037] Ce: It has the functions of purifying molten steel, modifying inclusions, and refining grains. A trace amount of Ce can reduce the passivation potential, widen the passivation range, increase the self-corrosion potential and polarization resistance of steel, and increase the density of the inner rust layer. In the present invention, the Ce content is controlled to be 0.0005-0.0050%.
[0038] At the same time, Ce can also purify the molten steel, reduce the segregation of S and P elements at the phase boundary, and make the distribution of alloy elements such as Cr, Ni and Mo in the two phases more uniform, thereby improving the material's CO2 corrosion resistance and improving toughness. Therefore, the present invention comprehensively studies the influence of Ce on each element and proposes an indicator control of (Cr+Cu / 3+Ni / 3+Mo+Ce×25) / (S+P)≥50. When (Cr+Cu / 3+Ni / 3+Mo+Ce×25) / (S+P)<50, the corrosion rate of the material is high and the toughness is poor.
[0039] In general, the present invention adopts the design ideas of the above components:
[0040] 1. Based on the design of low Cr content, Mn-Cu-Ni-Mo multi-element alloy is added for strengthening, and Nb-Ti-V microalloying is used to promote grain refinement, so that the material has good strength and toughness, good welding performance and economy.
[0041] 2. Ultra-pure steel is obtained by controlling extremely low inclusion elements such as S, P, B, O, and N. The Ca treatment process is used to modify the inclusions. The Ca / S ≥ 1.5 is achieved through a stable calcium feeding treatment process to reduce the content of non-metallic inclusions in the steel. The center segregation of the ingot is improved by combining light reduction and other technologies, reducing core inclusions and component segregation, thereby obtaining better low-temperature toughness.
[0042] 3. By adding Cu, Ni and Mo elements, the self-corrosion potential of the alloy is increased and the corrosion tendency is reduced; at the same time, a trace amount of Ce is added to purify the molten steel, and (Cr+Cu / 3+Ni / 3+Mo+Ce×25) / (S+P)≥50 is controlled to reduce the segregation of S and P elements at the phase boundary, and to make the distribution of alloy elements such as Cr, Ni and Mo more uniform, thereby reducing the passivation potential, widening the passivation range, increasing the polarization resistance and the density of the inner rust layer, and improving the material's CO2 corrosion resistance.
[0043] 4. Control the important alloy elements 0.8≤(Nb+V+Ti) / (C+N+5×B)≤2.5 to ensure the fine and uniform dispersion of suitable second phase particles such as NbTi(CN) and improve the solid solution of Cr, thus fully improving the low temperature toughness and CO2 corrosion resistance of the material.
[0044] The method for manufacturing X65 pipeline steel for service in a supercritical CO2 environment of the present invention comprises the following steps:
[0045] 1) Smelting and casting
[0046] Smelting, refining and casting into slabs according to the above ingredients;
[0047] 2) Rolling
[0048] Heating temperature: 1100-1250℃, rough rolling and final rolling temperature: 900-1000℃, finishing rolling and final rolling temperature: 750-880℃, finishing rolling cumulative reduction ratio ≥75%;
[0049] 3) Cooling
[0050] Cooling start temperature: 700-800℃, cooling stop temperature: 300-450℃, cooling rate: 10-30℃ / s.
[0051] Preferably, step 1) refining adopts LF and RH refining. During LF refining, the stirring time after all the alloys are added is controlled to be ≥5min, the RH calcium wire feeding amount is 300-500m, and the Ca / S ratio is controlled to be ≥1.5.
[0052] Preferably, step 1) is performed by continuous casting, the continuous casting calming time is ≥3 min, and the pulling speed fluctuation is ≤0.1 m / min.
[0053] Preferably, in step 2), 900°C≤rough rolling final rolling temperature<920°C, and the pass reduction rate is ≥15%; 920°C≤rough rolling final rolling temperature<950°C, and the pass reduction rate is ≥14%; 950°C≤rough rolling final rolling temperature≤1000°C, and the pass reduction rate is ≥11%.
[0054] In the manufacturing method of the present invention:
[0055] Refining uses LF treatment for desulfurization to reduce the S content in the steel, and RH treatment process to modify inclusions such as MnS and Al2O3 in the steel to reduce the inclusion elements in the steel. By increasing the effective calcium content in the steel, high-melting point CaS is formed in advance during the solidification of the molten steel, the total amount of MnS generated in this process is suppressed, and all or part of it is modified into CaS. On the other hand, large-particle Al2O3 inclusions are converted into low-melting point composite inclusions, which promote their floating and purify the internal quality of the molten steel. In the present invention, the LF stirring time is ≥5min, the RH silicon calcium wire feeding amount is 300-500m, and the Ca / S ratio is controlled to be ≥1.5. Through LF+RH double treatment, ultra-pure steel with low inclusions is obtained, and the accurate target design composition can be obtained after fine-tuning the composition.
[0056] Stable control of the calming time and drawing speed during continuous casting plays an important role in improving the quality of slabs, improving steel quality and structural segregation. Since Ce is added in the present invention, it is necessary to control and reduce the content of inclusions such as Ce, and ensure low inclusion element contents such as O≤0.0030%, N≤0.0050%, and H≤0.0002%. Therefore, the present invention controls the calming time ≥3min to allow relevant inclusions or gases in the steel to fully float up and be discharged. And control the fluctuation of the drawing speed ≤0.1m / min to stably control the casting, reduce the center segregation of the slab, and improve the uniformity of the slab quality, thereby improving the low-temperature toughness and performance uniformity of the final finished steel plate.
[0057] Slab heating temperature: 1100~1250℃. Sufficient heating temperature ensures full solid solution and heating uniformity of the alloy, which is conducive to obtaining uniform structure and plate shape. Dynamic recrystallization can eliminate the stress and fragmented grain boundaries caused by deformation, make the material fine and uniform again, and enhance the toughness and plasticity of the material, but it needs to reach a critical deformation amount and a higher deformation temperature. The lower the rolling temperature, the higher the reduction rate required for dynamic recrystallization.
[0058] In the present invention, the rough rolling and finishing temperature is controlled at 900-1000°C. The pass reduction rate is matched and controlled according to the rough rolling and finishing temperature: 900°C≤rough rolling and finishing temperature<920°C, the pass reduction rate is ≥15%; 920°C≤rough rolling and finishing temperature<950°C, the pass reduction rate is ≥14%; 950°C≤rough rolling and finishing temperature≤1000°C, the pass reduction rate is ≥11%, because with the movement of dislocations, etc., energy accumulates continuously, and dynamic recrystallization will occur after the strain reaches a critical value, that is, dynamic recrystallization is a thermal activation process, based on the stress-strain curve characteristic study based on the composition of the present invention, the thermal deformation activation energy is determined, and then according to different deformation temperature ranges, the minimum critical deformation amount required to be reached is further determined, thereby ensuring that dynamic recrystallization can occur, and at the same time, the occurrence of dynamic recrystallization causes the grains to break, so that the precipitation phases such as NbTi (CN) are obviously refined and dispersed, further refining the grains and improving the toughness of the material.
[0059] The finishing rolling temperature is controlled at 750-880°C, and the finishing rolling cumulative reduction rate is ≥75%. The dislocation nucleation points are increased by the rolling temperature and the large reduction rate, and the precipitation of NbTi(CN) is promoted to refine the grains. Since 0.025-0.055% Nb is added in the composition design of the present invention, the γ→α phase transformation is suppressed during the cooling process after rolling, the grain boundary ferrite is refined, and the granular bainite transformation is promoted. The post-rolling cooling temperature is controlled at 700-800°C, and the high cooling rate is in the range of 10-30°C / s, so that the content of bainite is increased; in addition, the final cooling temperature is controlled in the range of 300-450°C to increase the cooling permeability and improve the uniformity of the structure in the thickness direction, and finally a composite structure of granular bainite + blocky ferrite + pearlite + MA is obtained, and the content of granular bainite structure is ≥85%. The staggered distribution of high-angle grain boundary lath bundles in different orientations in granular bainite can effectively refine the grains and improve the strength and toughness of the material. In addition, the presence of blocky ferrite in the structure is conducive to improving the overall deformation coordination ability of the structure and inhibiting crack propagation, improving the low-temperature toughness of the material, but when its content exceeds 15%, it will aggravate the inhomogeneity of the structure, and it is easy to form a segregation zone in the core, reducing the overall strength and toughness of the material. Compared with bainite structure, blocky ferrite and pearlite structure are more easily corroded, weakening the overall corrosion resistance of the material.
[0060] Compared with the prior art, the present invention has the following advantages:
[0061] The composition design of the present invention adopts an ultra-low Cr content design, adds Mn-Cu-Ni-Mo multi-element alloy for strengthening, adds trace amounts of Ce, etc., and promotes grain refinement through Nb-Ti-V microalloying, so that the material has good strength and toughness, resistance to supercritical CO2 corrosion, and good welding performance and economy. Most of the existing CO2 pipeline materials use a higher Cr content, the alloy cost is high and leads to higher temper brittleness and poor welding performance, which brings greater costs and failure risks to long-distance pipelines. In addition, although some materials use a lower Cr content, there is no better measure to compensate for the performance loss, and the low-temperature toughness and corrosion resistance are relatively poor.
[0062] In the present invention, based on the austenite continuous cooling transformation characteristics of the current Cr-Mn-Cu-Ni-Mo multi-alloy and Nb-Ti-V microalloying components, the refinement and precipitation of precipitated phases such as NbTi (CN) are promoted through precise control during the rolling process, and the grains are further refined and the toughness of the material is improved. Combined with the subsequent cooling control, a higher cooling rate and a lower final cooling temperature are adopted to promote the formation of bainite, and improve the uniformity of the organization to finally obtain a uniformly refined target organization without obvious segregation, wherein the content of granular bainite organization is ≥85%, and the rest is a small amount of blocky ferrite, pearlite and MA, so that the steel has good low-temperature toughness, CO2 corrosion resistance, good welding performance and economy.
[0063] The R of the pipeline steel of the present invention t0.5 Yield strength 450~570MPa, tensile strength 540~700MPa, yield strength ratio ≤0.93, A 50 mm elongation ≥ 35%, -56℃ Charpy impact energy KV8 ≥ 300J, -46℃ DWTT SA% ≥ 85%. Compared with the existing main materials, it has better low-temperature toughness; at the same time, the material has good corrosion resistance, and the average corrosion rate in the supercritical CO2 phase under 8MPa, 50℃ saturated water conditions is ≤ 0.06mm / a. DETAILED DESCRIPTION
[0064] The present invention will be further described below in conjunction with the embodiments.
[0065] The chemical composition of the steel of the embodiment of the present invention is shown in Table 1 and Table 2, and the balance includes Fe and unavoidable impurities; the specific process parameters are shown in Table 3. The mechanical properties and microstructure results of the steel plates of the embodiment of the present invention and the comparative example are shown in Table 4.
[0066] It can be seen from Table 4 that the R t0.5 Yield strength 450~570MPa, tensile strength 540~700MPa, yield strength ratio ≤0.93, A 50 mm elongation ≥ 35%, -56℃ Charpy impact energy KV8 ≥ 300J, -46℃ DWTT SA% ≥ 85%, average corrosion rate in supercritical CO2 phase under 8MPa, 50℃ saturated water conditions ≤ 0.06mm / a.
[0067] In the pipeline steel of Comparative Example 1, (Nb+V+Ti) / (C+N+5*B) is less than 0.8, the cumulative reduction rate of finishing rolling is low, and the feed amount of calcium silicon wire is low, resulting in low Ca / S, and Ce is lower than the control requirement of the present invention.
[0068] In the pipeline steel of Comparative Example 2, (Nb+V+Ti) / (C+N+5*B)>2.5, (Cr+Cu / 3+Ni / 3+Mo+Ce*25) / (S+P)<50, the reduction rate of the final pass of rough rolling is low, and Ce is also lower than the control requirement of the present invention.
[0069] The -56°C Charpy impact energy and -46°C DWTT SA of Comparative Examples 1 and 2 both showed low single values, and the supercritical CO2 corrosion rates were both high.
[0070]
[0071]
[0072]
[0073]
Claims
1. An X65 pipeline steel for supercritical CO2 environment, the chemical composition weight percentage of which is: C: 0.02-0.07%, Si: 0.10-0.30%, Mn: 0.80-1.45%, P≤0.0080%, S≤0.0015%, Cu: 0.05-0.35%, Ni: 0.05-0.30%, Cr: 0.20-0.80%, Mo: 0-0.09%, Nb:
0. 025~0.055%、V:0~0.05%、Ti:0.005~0.020%、Ca:0.0010~0.0040%、Alt:0.010~0.040%、B≤0.0004%、O≤0.0030%、N≤0.0050%、H≤0.0002%、Ce:0.0005~0.0050%、the balance includes Fe and other unavoidable impurities, and at the same time meet the following requirements: Ca / S≥1.5; Nb+V+Ti≤0.12%; 0.8≤(Nb+V+Ti) / (C+N+5×B)≤2.5; (Cr+Cu / 3+Ni / 3+Mo+Ce×25) / (S+P)≥50.
2. The X65 pipeline steel for supercritical CO2 environment service as claimed in claim 1 is characterized in that: The balance is Fe and other inevitable impurities.
3. The X65 pipeline steel for supercritical CO2 environment service as claimed in claim 1 or 2, characterized in that: The microstructure of the pipeline steel is uniformly refined granular bainite+blocky ferrite+pearlite+MA, wherein the content of granular bainite is ≥85%.
4. The X65 pipeline steel for supercritical CO2 environment service as claimed in claim 1, 2 or 3, characterized in that: The R of the pipeline steel t0.5 Yield strength 450~570MPa, tensile strength 540~700MPa, yield strength ratio ≤0.93, A 50 mm elongation ≥ 35%, -56℃ Charpy impact energy KV8 ≥ 300J, -46℃ DWTT SA% ≥ 85%, average corrosion rate in supercritical CO2 phase under 8MPa, 50℃ saturated water conditions ≤ 0.06mm / a.
5. The method for manufacturing X65 pipeline steel for service in supercritical CO2 environment according to any one of claims 1 to 4, characterized in that: The steps include: 1) Smelting and casting Smelting, refining and casting into slabs according to the composition of claim 1 or 2; 2) Rolling Heating temperature: 1100-1250℃, rough rolling and final rolling temperature: 900-1000℃, finishing rolling and final rolling temperature: 750-880℃, finishing rolling cumulative reduction ratio ≥75%; 3) Cooling Cooling start temperature: 700-800℃, cooling stop temperature: 300-450℃, cooling rate: 10-30℃ / s.
6. The manufacturing method according to claim 5, characterized in that: Step 1) LF and RH refining are adopted for refining. During LF refining, the stirring time after all the alloys are added is controlled to be ≥5min, the RH calcium wire feeding amount is 300-500m, and the Ca / S ratio is controlled to be ≥1.
5.
7. The manufacturing method according to claim 5, characterized in that: Step 1) casting is carried out by continuous casting, the continuous casting calming time is ≥3min, and the pulling speed fluctuation is ≤0.1m / min.
8. The manufacturing method according to claim 5, characterized in that: In step 2), 900°C≤rough rolling final rolling temperature<920°C, and the pass reduction rate is ≥15%; 920°C≤rough rolling final rolling temperature<950°C, and the pass reduction rate is ≥14%; 950°C≤rough rolling final rolling temperature≤1000°C, and the pass reduction rate is ≥11%.
Citation Information
Patent Citations
Cutting tool for the continuous machining of metals and the method of making same
CA1000040A
Preparation method for CO2 corrosion resistant pipeline steel used for surface gathering
CN103320705B
A pipeline steel with excellent CO2 corrosion resistance and its production method
CN105132822B
Low-Cr economical X65 pipeline steel capable of resisting CO2 corrosion and production method
CN106498279A
A CO2-resistant steel plate and its preparation method
CN112941422B